Early cretaceous bimodal volcanic rocks in Wuga Co area, central tibet: The first identification of direct products derived from slab sinking in the Bangong-Nujiang suture zone - Chen, Wei; Liu, Zhibo; Wang, Nan; Wang, Genhou; Zheng, Ming; Han, Ning; Hu, Yiling; Yan, Xukun (Frontiers in Earth Science, 2023)
The Bangong–Nujiang Suture Zone (BNSZ) in central Tibet is a remnant of the Bangong–Nujiang Ocean that records its entire Wilson Cycle. The model of divergent double-sided subduction (DDS) is crucial for elucidating the evolution of tectonomagmatic activity on both sides of the BNSZ and for understanding why no high-pressure metamorphic rocks occur in the BNSZ. However, the DDS geodynamics remain poorly constrained. In particular, there is a lack of reports on magmatic rocks directly associated with slab sinking in the DDS terminal stage. This study presents new geochronological, geochemical, and isotopic data for the Early Cretaceous bimodal volcanic rocks around the Wuga Co area. The bimodal volcanic rocks are divided into the Wuga Co rhyolites (SiO2 = 77.0–79.0 wt.%) and the Wuga Co basaltic andesites (SiO2 = 53.9–55.5 wt.%). The isotopic values of the Wuga Co basaltic andesites with low (87Sr/86Sr)i values (+0.7040 to +0.7044) and high εNd(t) values (+3.8 to +4.1) lie among three endmembers (the BNO sediments in accretionary wedge, depleted mantle and the BNO slab). These values indicate the partial melting of a mantle peridotite that interacted with the subducted slab and sediment in the accretionary wedge, which was caused by the sinking of the Bangong–Nujiang oceanic slab. The Wuga Co rhyolites (108 Ma) have low (87Sr/86Sr)i values (+0.703 to +0.706), high εNd(t) values (+2.25 to +2.49), and high εHf(t) values (+5.6 to +10.0). These values indicate that the rhyolite formed by partial melting of juvenile basaltic crust. This study also collected Hf isotope data from both sides of the BNSZ to constrain its evolution. Our results show that the εHf(t) values of magma on both sides of the BNSZ were elevated simultaneously at 130 Ma, which may be caused by the Bangong–Nujiang oceanic slab rupture. Based on these new data, we propose that the Bangong–Nujiang oceanic slab ruptured from the two overlying terranes at approximately 130 Ma and subsequently sank into the mantle at approximately 108 Ma.